2021
DOI: 10.1016/j.ebiom.2021.103345
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared photoimmunotherapy targeting human-EGFR in a mouse tumor model simulating current and future clinical trials

Abstract: Background: near-infrared photoimmunotherapy (NIR-PIT) is a cancer treatment that uses antibody-photoabsorber (IRDye700DX, IR700) conjugates (APCs) which bind to target cells and are photoactivated by NIR light inducing rapid necrotic cell death. NIR-PIT targeting human epidermal growth factor receptor (hEGFR) has been shown to destroy hEGFR expressing human tumor cells and to be effective in immunodeficient mouse models. NIR-PIT can also be targeted to cells in the tumor microenvironment, for instance, CD25-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Even in primary tumors, if the initial treatment is only partially successful, repeated endoscopic NIR‐PITs can be performed on the same site at a later time. In mouse models, cancer cell‐targeted NIR‐PIT has been proved to enhance antitumor immune response by releasing various kinds of tumor‐associated antigens (TAAs), 30 , 31 that could help to treat satellite or distant lesions. Repeated NIR‐PITs could work as immune boosters, although such effects are currently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Even in primary tumors, if the initial treatment is only partially successful, repeated endoscopic NIR‐PITs can be performed on the same site at a later time. In mouse models, cancer cell‐targeted NIR‐PIT has been proved to enhance antitumor immune response by releasing various kinds of tumor‐associated antigens (TAAs), 30 , 31 that could help to treat satellite or distant lesions. Repeated NIR‐PITs could work as immune boosters, although such effects are currently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kim et al 33 cross-linked Ce6 with many targeted molecules, including trastuzumab (1:1), by NHS-activated ester and obtained a new conjugate with better tissue penetration and a 6-fold increase in tumor accumulation. A large number of basic studies 8 , 34 , 35 have shown that NIR-PIT has high targeting ability and few adverse reactions, but the current experiments are mostly at the cellular and animal level ( Table 2 ), and there are relatively few clinical studies ( Table 1 ). Therefore, large-scale clinical trials are needed to confirm the superiority of NIR-PIT in the treatment of malignant tumors.…”
Section: Photoimmunoconjugatementioning
confidence: 99%
“…NIR-PIT can target and treat almost any cell surface antigen in vivo and in vitro such as EGFR, 34 PSMA, 62 PD-L1, 63 CD44, 64 CD133 2 and so on. NIR-PIT directed at CD44 and CD133, 2 which are considered effective in breast cancer and glioblastoma, respectively.…”
Section: Opportunities and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one day after intravenous infusion of an IR700-based APC, NIR light is delivered to the cancer, activating a photochemical reaction that results in highly selective cancer cell killing while leaving normal tissues unaffected [ 4 , 5 , 6 , 7 ]. NIR-PIT has been used to target various cancer-specific proteins, such as epidermal growth factor receptor (EGFR) [ 8 , 9 , 10 , 11 , 12 , 13 ] and human epidermal growth factor receptor-2 (HER2) [ 14 , 15 , 16 , 17 , 18 , 19 ], and both have shown excellent anti-cancer effects. Furthermore, the clinical use of EGFR-targeted NIR-PIT progressed into clinical trials of patients with head and neck squamous cell carcinoma (HNSCC).…”
Section: Introductionmentioning
confidence: 99%